Variability of nucleolus organizer region sizes in green frog karyotypes - Бірюк, О. В.; Розанов, Ю. М.; Литвинчук, С. М.; Пасинкова, Р. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Search for species-specific markers on chromosomes of the lake (Pelophylax ridibundus) and the pond (P. lessonae) frogs is an actual problem to study the cytogenetic mechanisms of hemiclonal inheritance in hybrid frog, P. esculentus. In this paper the method of Ag-staining was used. The variability of nucleolus organizer region (NOR) sizes in 65 individuals of parental species and hybrids from 22 localities was studied. We found no significant differences in the relative length of NORs on parental species chromosomes. We also assumed that NOR relative length in hybrids is more asymmetrical if compared with parental species. This suggestion was not confirmed as well. Therefore we concluded that the length of NOR cannot be used as reliable species-specific marker. Cases of NOR doubling and deviations from the normal number of NORs in hybrid karyotypes were recorded.